Respostas
respondido por:
1
2 x + 5 y = 13
-2 x + 7 y = 23
-----------------------
0 + 12 y = 36
12 y = 36
y = 36/12
y = 3
encontrando o valor de x
2 x + 5 y = 13
2 x + 5 . 3 = 13
2 x + 15 = 13
2 x = 13 - 15
2 x = -2
x = -2/2
x = -1
-2 x + 7 y = 23
-----------------------
0 + 12 y = 36
12 y = 36
y = 36/12
y = 3
encontrando o valor de x
2 x + 5 y = 13
2 x + 5 . 3 = 13
2 x + 15 = 13
2 x = 13 - 15
2 x = -2
x = -2/2
x = -1
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás